Biparietal Diameter–to–Crown‐Rump Length Disproportion in First‐Trimester Fetuses With Holoprosencephaly. (1st July 2014) - Sepulveda, Waldo; Wong, Amy E.; Andreeva, Elena; Odegova, Natalia; Martinez-Ten, Pilar; Meagher, Simon
Abstract : Objectives: To determine whether the biparietal diameter measurement is altered in first‐trimester fetuses with holoprosencephaly. Methods: Cases of holoprosencephaly were collected retrospectively from 4 fetal medicine centers, and first‐trimester biparietal diameter measurements were reviewed. The diagnosis of holoprosencephaly was established sonographically by the detection of abnormal choroid plexus morphologic characteristics (absent "butterfly" sign) and the identification of a monoventricular cerebral cavity on axial views of the fetal brain. The proportion of fetuses with biparietal diameter measurements below the 5th percentile for crown‐rump length was determined. Results: Among 45 cases of holoprosencephaly reviewed, 43 had information on both biparietal diameter and crown‐rump length measurements. The biparietal diameter was below the 5th percentile for crown‐rump length in 14 (32.6%) fetuses. Chromosomal analysis was available in 41; no statistically significant difference in biparietal diameter measurement between those with associated chromosomal anomalies and those without anomalies was noted. A supplementary analysis using head circumference measurement showed an even greater proportion of fetuses with holoprosencephaly with measurements below the 5th percentile for crown‐rump length (18 of 42 [42.9%]). Conclusions: One‐third of first‐trimester fetuses with a sonographic diagnosis of holoprosencephaly had a biparietal diameter that was smaller than expected for crown‐rump length. In this subset of fetuses, the evaluation of intracranial anatomy for signs of holoprosencephaly may be more difficult to perform due to the smaller size of the brain. Therefore, the detection of a biparietal diameter below the 5th percentile as expected from crown‐rump length on the first‐trimester scan may be a warning sign of holoprosencephaly and should prompt a detailed examination of the intracranial anatomy.